"Croatia" - Palekčić, Marko; Zekanović, Nenad (2007)
This paper contains basic information about system of education in Croatia. The chapter History of the school system presents cultural context and the corner stones of the historical developments of schooling and reforms and innovations during the past 30 years. Socio-cultural context of the current school system designates to educational targets and general function of school, socio-economic context, social position of teaching profession and the role of family in the school education. Organizational context and governance contains the information about basic legal principles, levels and philosophy of the governance, financing, relation public – private schooling, general standards, quality management and support of the school system. The special attention was paid to the structure and characteristics of the current (pre-primary, primary, lower and upper secondary and special) school education: school form(s), its main goals/functions, strategies and programs for special support of minority children, slow learners and migrants children, integration, learning support, European dimension in school problems, school life, extracurricular programs and inter-levels transition. Postsecondary and tertiary education describes general outline, forms, vertical/horizontal differentiation, latest developments/tendencies and reference to teacher training. The last chapter directs attention to current problems, discussion and perspectives of development of education in Croatia. The Appendix contains basic statistical data (percentage of the population in the single school form/type, majority/minority pupils/students in the total enrolment, school time and distribution of teaching time devoted to subject/subjects groups).
Projekt MZOS
ENG